2009
DOI: 10.1248/bpb.32.937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antiangiogenic Effects of 2-Aryl-3-bromoquinolin-4(1H)-ones and a NCH3-4-oxo Derivative

Abstract: 2-Aryl-3-bromoquinolin-4(1H)-ones and 2-aryl-3-bromo-1-methylquinolin-4(1H)-one were evaluated for their antiangiogenic effects. Results showed that the 2-aryl-3-bromoquinolin-4(1H)-ones (QNHFBr and QNHClBr), and the 3-bromo-2-(4-chlorophenyl)-1-methylquinolin-4(1H)-one (QNMeClBr) reduced endothelial cell numbers in an assay of cell proliferation, showing increased cytotoxicity at higher doses. The compounds also inhibited neovessel growth in an ex vivo assay of angiogenesis. Furthermore, low levels of proangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Our results also showed that compound A leads to a degeneration of the vascular network inhibiting blood vessel formation, demonstrating a direct effect of the compound on angiogenesis. This was also corroborated by the quinoline-3-carboxamide linomide and its derivatives in in vivo CAM assays and by new bromoquinoline derivatives [34,38].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our results also showed that compound A leads to a degeneration of the vascular network inhibiting blood vessel formation, demonstrating a direct effect of the compound on angiogenesis. This was also corroborated by the quinoline-3-carboxamide linomide and its derivatives in in vivo CAM assays and by new bromoquinoline derivatives [34,38].…”
Section: Discussionmentioning
confidence: 57%
“…On the other hand, acrylate group substitutions on benzofurane structures were preferred for the antiproliferative activity of HUVEC cells [32]. It is also important to note that these structures have also been proposed as DNA-intercalating agents, inhibitors of angiogenesis, and inductors of apoptosis [5,10,33,34], demonstrating pleiotropic modes of action of these compounds. However, there is no information available on compounds that share both chemical groups as potential antitumor agents in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of quinolines and acrylates as potential anticancer agents have been previously demonstrated 3,4 ; however, there are few data available about the effect of these combined structures on tumour cells. It has been recently reported the potential antitumour properties of different quinoline acrylate derivatives 7 , and especial attention has been paid to (E)-Methyl 2-(7-chloroquinolin-4-ylthio)-3-(4-hydroxyphenyl) acrylate (QNACR), due to its ability to inhibit cell adhesion, migration, invasion, angiogenesis matrix metalloproteases in vitro and tumour growth in vivo 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, quinoline derivatives have shown effects as antineoplastics such as tasquinimod (ABR-215050) which is one of the main quinoline compounds that is currently in clinical research whose effects are related to the inhibition of angiogenesis in patients with tumour metastasis 1 . On the other hand, substitutions with an acrylate group on organic structures such as benzofuranes improves the antitumour activity in vitro 2 , being proposed as potential DNA-intercalating compounds, inhibitors of angiogenesis and apoptosis inducers 3,4 confirming the multi-target effects of these structures.…”
Section: Introductionmentioning
confidence: 99%